GE_GERICHTE P/13461/2012 vom 30. Juni 2015 - GE Cour de justice (2015)
IN DUBIO PRO REO; PRÉSOMPTION D'INNOCENCE; INJURE; VOIES DE FAIT; EXEMPTION DE PEINE; AVOCAT; HONORAIRES | CP.177.1; CP.126.1; CPP.391.2; CPP.429.1; CPP.428.1; CPP.428.3; CPP.426.1